PHYSIOLOGICAL AND HEMATOLOGICAL ADAPTATIONS TO ENDURANCE TRAINING IN ELITE MIDDLE AND LONG-DISTANCE RUNNERS: IMPLICATIONS FOR PERFORMANCE OPTIMIZATION - Nigatu Worku Angasu; Aschenaki Taddese; Zeru Bekele Tola (Sport Scientific And Practical Aspects, 2025)
Endurance training (EnT) is a critical component for elite middle and long-distance runners, necessitating a comprehensive examination of the hematological and physiological adaptations that occur throughout a training cycle. This study investigated the effects of EnT on various physiological and hematological factors that influence running performance. A well-structured training program with dynamic intensities and intervals was developed. A quasi-experimental approach was used to conduct pre- and post-tests. The key findings revealed substantial improvements, particularly in erythrocyte volume and hemoglobin (Hgb) mass. Specifically, the RBC count increased significantly from a pre-training mean of 5.18 (±0.40) million/L to 5.45 (±0.39) million/L post-training (t = 5.23, P = 0.001). Furthermore, maximal oxygen consumption (VO2max) demonstrated a marked increase from 71.9 (±1.27) to 78.4 (±2.02) ml/kg/min (t = 16.24), indicating enhanced aerobic capacity. In addition to these improvements, resting heart rate (RHR) exhibited a significant reduction, decreasing from 57 (±3) to 53 (±4) beats per minute (bpm) (t = 4.48, P = 0.001). Collectively, these physiological enhancements accounted for an impressive explanatory power of 86.9% for performance outcomes, particularly evident in the 5000m time trial (TT). These results underscore the importance of EnT programs in optimizing performance for elite runners, highlighting the need of individualized training regimens that promote the physiological adaptations essential for maximizing athletic potential.